Naskah Pengobatan “Usada” di Bali dan Problematika Pemurnian Teks - I Wayan Suardiana (Pusat Kajian Bali Universitas Udayana, 2018)
This article examines Balinese text of usada genre as a basis for traditional medicine and as a model of the text purification. The importance of this study is done considering that in maintaining health or treating diseases, people consume chemical and herbal medicine as an alternative. Despite of the high prices of medicines and herbals, Balinese people rarely use herbal ingredients recommended in the usada text. Furthermore, usada texts that circulated in public contain many mistakes and consequently errors in selecting medicinal ingredients. This study uses qualitative data by comparing three texts from the Usada Cukil Daki manuscripts. The theory used to study is the traditional philology to get the case of incorrect copying of Balinese letter text to Latin letters. The results obtained indicate that there are many errors in the copy and wrong writing in the decrease in text.